In Vitro and In Vivo Antimalarial Activity of Ficus thonningii Blume (Moraceae) and Lophira alata Banks (Ochnaceae), Identified from the Ethnomedicine of the Nigerian Middle Belt - M. O. Falade; D. O. Akinboye; G. O. Gbotosho; E. O. Ajaiyeoba; T. C. Happi; O. O. Abiodun; A. M. J. Oduola (Journal of Parasitology Research)
Drug resistance in Plasmodium falciparum requires that new drugs must be developed. Plants are a potential source for drug discovery and development. Two plants that used to treat febrile illnesses in Nigeria were tested for in vitro and in vivo antimalarial activity and cytotoxicity in cancer cell lines. Methanol, hexane, and ethyl acetate leaf extracts of Ficus thonningii and Lophira alata were active in in vitro assays against P. falciparum NF54 (sensitive) and K1 (multiresistant) strains. Hexane extracts of F. thonningii and L. alata were the most effective extracts in in vitro assays with IC50 of 2.7±1.6 μg/mL and 2.5±0.3 μg/mL for NF54 and 10.4±1.6 μg/mL and 2.5±2.1 μg/mL for K1 strain. All extracts were nontoxic in cytotoxicity assays against KB human cell line with IC50 of over 20 μg/mL, demonstrating selectivity against P. falciparum. In vivo analysis shows that hexane extracts of both plants reduced parasitaemia. At the maximum dose tested, L. alata had a 74.4% reduction of parasitaemia while F. thonningii had a reduction of 84.5%, both extracts prolonged animal survival in mice infected with P. berghei NK65 when compared with vehicle treated controls. The antiplasmodial activity observed justifies the use of both plants in treating febrile conditions.